Child Disability and Deprivation: A Conceptual, theoretical and empirical review of the sub-Saharan African literature - (:unkn) unknown (My University, 2022)
The nexus between disability and deprivation is an increasing interest to policy makers as children with disabilities are being mainstreamed into national and international poverty reduction programs. This literature is vast and has a long history, however, previous literature reviews have not addressed the concepts of poverty and deprivation especially for children living with disabilities in Africa. The aim of this chapter was to provide a comprehensive survey on links between child disability and deprivation in Africa. It shows that the International Classification of Functioning, Disability and Health for Children and Youth (ICF-CY) is today almost universally recognised as the framework to understand child disability. The Washington Group/UNICEF child functioning screening instrument is now well endorsed to measure disability in children aged 2-17 years, even though not yet routinely integrated into national surveys. The theoretical review highlights the diversity of theoretical framework used in economics and social science studies, while empirical literature showed that children with disability are living a vicious circle of social and material deprivation. By drawing attention to these findings and their limitations, this chapter provides suggestions for future research in order to provide policy makers relevant tools to improve the well-being of children living with disabilities.
Keywords: African Research